Association of Fibroblast Growth Factor Receptor 4 Genetic Polymorphisms With the Development of Uterine Cervical Cancer and Patient Prognosis. (January 2018) - Chen, Tze-Ho; Yang, Shun-Fa; Liu, Yu-Fan; Lin, Wea-Lung; Han, Chih-Ping; Wang, Po-Hui
This is the first study to investigate the relationships among fibroblast growth factor receptor 4 (FGFR4) genetic polymorphisms, development of uterine cervical cancer, clinicopathological variables, and patient prognosis in Taiwanese women. Real-time polymerase chain reaction and genotyping were used to detect the genotype frequencies of 4 FGFR4 single-nucleotide polymorphisms (SNPs), rs351855 (C/T, Gly388Arg), rs2011077 (G/A), rs7708357 (G/A), and rs1966265 (Ile10Val), in 138 patients with invasive cancer, 89 with precancerous lesions of uterine cervix, and 335 normal controls. The results showed that there is no significant difference in the frequencies of FGFR4 SNPs rs351855, rs2011077, rs7708357, and 1966265 between women with cervical invasive cancer and normal controls even after controlling for age. However, significant differences existed in the distributions of the FGFR4 genetic polymorphism rs2011077, when mutant homozygotes (AA) were compared using other genotypes (GG/GA) as a reference, as well as rs1966265, when mutant homozygotes (AA) were compared using GG/GA as a reference, between women with cervical precancerous lesions and normal women even after controlling for age. In multivariate analysis, lymph node metastasis was associated with cancer recurrence, and lymph node metastasis and FGFR4 rs351855 were associated with patient survival. In conclusion, our study demonstrated that FGFR4 rs2011077 and rs1966265 are associated with the progression of cervical normal tissues to precancerous lesions in Taiwanese women. Moreover, rs351855 (Gly388Arg) is the only FGFR4 genetic polymorphism that is associated with patient survival.